Analysis of Library Spatial Planning in Special Libraries - Zandia, Puja; Samosir, Fransiska Timoria; Sa’diyah, Lailatus (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2024)
This study aims to assess the physical and non-physical conditions of facilities and infrastructure at the Diplomatic Library of the Ministry of Foreign Affairs and determine whether they are in accordance with the National Standards for Special Libraries. Two librarians were involved as informants in this study. The method used was descriptive qualitative method using observation, interview, and documentation. The results showed that the layout of the Diplomatic Library, including coloring, lighting, and furniture, was good. However, noise is still heard in the library. Regarding air temperature regulation, it is good and comfortable, but the operation of the air conditioning system that does not stop for 24 hours is not suitable for the maintenance of collection materials. In terms of facilities and infrastructure, the Diplomatic Library of the Ministry of Foreign Affairs is in good condition and meets national library standards. However, the library space has not fully complied with the National Library Standard in terms of size. The significance of this study lies in its contribution to the improvement of the quality of the Diplomatic Library of the Ministry of Foreign Affairs. The findings are important as they provide research-based evidence of areas that require improvement to achieve full compliance with the National Standard for Specialized Libraries. The research also provides guidance to other library managers who wish to ensure that their facilities meet national standards.